O protagonismo juvenil na percepção de jovens em um programa de educação para o trabalho na cidade de Ribeirão Preto. - Esteves, Maria Cristina Durante (2005)
The teen protagonism is defined when the young is able to act in his/her family s circle, social and scholarship circle, being this act individual or in group. This study was carried out in order to identify the manner the Educational Working Program s learnings take place; verify if this learning helps the teen protagonism besides knowing the teens opinions and perceptions who took part of this program related to their rules in society. Teens inscribed in Ribeirão Preto s Educational Working Program took part of this study. Program inserted in Ribeirão Preto s National Comerce Learning Service (Serviço Nacional de Aprendizagem Comercial SENAC) which are linked to Ribeirão Preto s Mayor and the Educational Working Foundation. The data were collected from six focal groups that ocurred in September, 2004, involving fifty-six participants. The sessions were recorded according to teens and their responsibles authorizations. The discussions focused the teens perception in society, the meaning of taking part of this program and in other learning areas as well as the educational process in this program. The data were analyzed according to seven analysis categories: the teen s perception according to his rule in society, teen s participation, work and youthful, joy and the young, prevention, sexuality and drugs, learning and teaching and learning to life. The analysis showed some teens feel under pressure in having to help their families economically but in a program for young/teens they are able to learn for working and life. They stated there is a lack of spaces that could stimulate their participation in another activities and the act of creating these spaces would be important to their selfimprovement. They live with the violence s fear and mention the orientation s importance related to the sexually transmitted diseases prevention and pregnancy. They point these approaches should happen in a participative way, occasion in which they could be listened and give their opinions. We ought to think about learning spaces where the young/teens can occupy their protagonist rule, being able to have not only individual but collective transformations as well, generating changings in all social circles.